A Multi-Criteria Decision Analysis of Food Security Strategies in Remote Highland Communities: Evidence From Wouma Village, Papua Pegunungan, Indonesia - Tukijan Tukijan; Ayu Anggraini Tambunan; Achmad Nur Iman; M. Irvanni Bahri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Food insecurity remains a persistent challenge in the Papua Highlands of Indonesia, driven by geographic isolation, limited infrastructure, low agricultural productivity, and high dependence on external food supplies. This study aims to identify priority strategies for strengthening food security through a community-based local food system approach by applying the Analytic Hierarchy Process (AHP). The analysis is structured around the four dimensions of food security proposed by the Food and Agriculture Organization (FAO), namely availability, access, stability, and utilization. Data were collected from key stakeholders through pairwise comparison questionnaires, complemented by focus group discussions and in-depth interviews. The results indicate that food availability is the most dominant criterion, followed by access, stability, and utilization. Across all dimensions, Local Food Production emerges as the highest-priority alternative, highlighting the strategic importance of strengthening upstream agricultural capacity to ensure sufficient and sustainable food supply. Infrastructure and Market Access ranks second, emphasizing the role of transportation, storage, and market connectivity in improving distribution efficiency and affordability. Community-Based Food Institutions and Nutrition Programs and Social Protection function as complementary interventions, supporting governance, coordination, and the protection of vulnerable groups. The convergence of the AHP results with the FAO food security framework and the Food Security and Vulnerability Atlas (FSVA) of the Indonesian National Food Agency (BPN) confirms that structural strengthening of local food systems, supported by infrastructure development and institutional capacity building, constitutes the most effective pathway for enhancing food security and resilience in the Papua Highlands. These findings provide an evidence-based basis for formulating integrated and context-sensitive food security policies in remote and highland regions.